Seed germination ecology of itchgrass (Rottboellia cochinchinensis) - Bolfrey-Arku, Grace E-K.; Chauhan, Bhagirath S.; Johnson, David E. (Cambridge University Press, 2011)
Itchgrass is a weed of many crops throughout the tropics and one of the most important grass weeds of rainfed rice. Experiments were conducted in the laboratory and screenhouse to determine the effects of light, alternating day/night temperatures, high temperature pretreatment, water stress, seed burial depth, and rice residue on seed germination and seedling emergence of itchgrass in the Philippines. Two populations were evaluated and the results were consistent for both populations. Germination in the light/dark regime was greater at alternating day/night temperatures of 25/15 C than at 35/25, 30/20, or 20/10 C. Light was not a requirement for germination, but a light/dark regime increased germination by 96%, across temperature and population. A 5-min high temperature pretreatment for 50% inhibition of maximum itchgrass germination ranged from 145 to 151 C with no germination when seeds were exposed to ≥ 180 C. The osmotic potential required for 50% inhibition of maximum germination was −0.6 MPa for itchgrass, although some seeds germinated at −0.8 MPa. Seedling emergence was greatest for seeds placed on the soil surface, and emergence declined with increasing soil burial depth; no seedlings emerged from seeds buried at 10 cm. The addition of rice residue to soil surface in pots at rates equivalent to 4 to 6 Mg ha−1reduced itchgrass seedling emergence. Since seedling emergence was greatest at shallow depths and germination was stimulated by light, itchgrass may become a problem in systems where soil is cultivated at shallow depths. Knowledge gained in this study could contribute to developing components of integrated weed management strategies for itchgrass.